PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATA PELAJARAN KONSTRUKSI BANGUNAN GEDUNG PADA TINGKAT SMK - Shila Azka Khudzaifah (Jurnal Salome : Multidisipliner Keilmuan, 2023)
In the industrial era 4.0, the world of education is required to produce a curriculum whose dimension is critical reasoning. To develop critical thinking skills requires a habituation process carried out by the teacher. Where, the learning model that can be used is problem based learning. By applying problem based learning to students, students can get used to thinking critically about problems that occur in the real world. In building construction subjects, solutions are needed for all existing problems resulting from the failure of a building construction or imperfection in building results. This is very necessary to increase the understanding of vocational students, especially those majoring in building construction. By using problem based learning in building construction subjects, it is hoped that students can quickly understand and comprehend efforts to avoid failure in a building.